Optimisation Model based Dashboard for Managing Airport Aeronautical Revenues / Wan Mazlina Wan Mohamed and Adibah Shuib - Wan Mohamed, Wan Mazlina; Shuib, Adibah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Main sources of airport revenues are from aeronautical revenue and non-aeronautical revenues. Many airports put more emphasis on improving non-aeronautical revenues despite the fact that aeronautical revenue is still the main income contributor to most airports in sustaining their business. Airport’s aeronautical revenues depend on the number of air traffic where relatively high number of traffic is assumed to generate greater aeronautical revenues. However, seldom airports analyse the impact of various factors related to air traffic such as flight types, aircraft types, flight time and day, and types of passengers arriving or departing, which can indicate the trend in passenger’s preferences and potential aeronautical revenues. This research took into consideration these factors when developing the mathematical optimisation model, known as Aeronautical Revenue Optimisation Model (AROM), for generating maximum aeronautical revenues of regional airports. Based on the model and solutions, a Graphic User Interface (GUI) dashboard system has been developed for assessing the aeronautical revenue generated by different variables of the air traffic movements. The dashboard allows user to extract existing data, run the model and view results, including the potential revenue generated by each aircraft. Thus, it provides managers with in-depth information of each flight and its impact on potential revenue generation, which guides them in decision making, operations planning and improving the billing efficiency.